Sex-based Difference in Response to Recombinant Human Bone Morphogenetic Protein-2 in a Rat Posterolateral Fusion Model. Issue 23 (1st December 2022) - Foley, James P.; Fred, Elianna J.; Minardi, Silvia; Yamaguchi, Jonathan T.; Greene, Allison C.; Furman, Andrew A.; Lyons, Joseph G.; Paul, Jonathan T.; Nandurkar, Tejas S.; Blank, Kenneth R.; Havey, Robert M.; Muriuki, Muturi; et al.
Abstract : Study Design: This was a preclinical study. Objective: Evaluate sex-dependent differences in the bone healing response to recombinant human bone morphogenetic protein-2 (rhBMP-2) in a rat posterolateral spinal fusion model. Summary of Background Data: Minimal and conflicting data exist concerning potential sex-dependent differences in rhBMP-2-mediated bone regeneration in the context of spinal fusion. Materials and Methods: Forty-eight female and male Sprague-Dawley rats (N=24/group), underwent L4–L5 posterolateral fusion with bilateral placement of an absorbable collagen sponge, each loaded with 5 µg of bone morphogenetic protein-2 (10 µg/animal). At eight weeks postoperative, 10 specimens of each sex were tested in flexion-extension with quantification of range of motion and stiffness. The remaining specimens were evaluated for new bone growth and successful fusion via radiography, blinded manual palpation and microcomputed tomography (microCT). Laboratory microCT quantified bone microarchitecture, and synchrotron microCT examined bone microstructure at the 1 µm level. Results: Manual palpation scores differed significantly between sexes, with mean fusion scores of 2.4±0.4 in females versus 3.1±0.6 in males ( P <0.001). Biomechanical stiffness did not differ between sexes, but range of motion was significantly greater and more variable for females versus males (3.7±5.6° vs. 0.27±0.15°, P <0.005, respectively). Laboratory microCT showed significantly smaller volumes of fusion masses in females versus males (262±87 vs. 732±238 mm 3, respectively, P <0.001) but significantly higher bone volume fraction (0.27±0.08 vs. 0.12±0.05, respectively, P <0.001). Mean trabecular thickness was not different, but trabecular number was significantly greater in females (3.1±0.5 vs. 1.5±0.4 mm −1, respectively, P <0.001). Synchrotron microCT showed fine bone structures developing in both sexes at the eight-week time point. Conclusions: This study demonstrates sex-dependent differences in bone regeneration induced by rhBMP-2. Further investigation is needed to uncover the extent of and mechanisms underlying these sex differences, particularly at different doses of rhBMP-2.